2012
DOI: 10.1136/neurintsurg-2012-010477
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral vasospasm following tumor resection

Abstract: 'Cerebral vasospasm' after tumor resection is a rare but challenging complication with very high morbidity and mortality in reported cases. Vasospasm following brain tumor surgery shares some of the same clinical variables (time interval, causative factors, morbidity and death rates) of vasospasm after aneurysmal subarachnoid hemorrhage. A high index of suspicion is required for early diagnosis and prompt management which are key elements of final outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 66 publications
4
76
0
Order By: Relevance
“…In the first case, the vasospasm would be triggered mechanically by the surgeon, and in the second case, it would result from the vasoactive effect of hemoglobin metabolites, as in the case of an aneurysmal SAH. Indeed, the majority of cases in the literature concern tumors in proximity to the basal cisterns or surgical procedures that have allowed blood to accumulate around the major cerebral vessels in the basal cisterns (2,7,22). In most previously reported cases, neurological deterioration occurred between 5 and 10 days after resection of the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first case, the vasospasm would be triggered mechanically by the surgeon, and in the second case, it would result from the vasoactive effect of hemoglobin metabolites, as in the case of an aneurysmal SAH. Indeed, the majority of cases in the literature concern tumors in proximity to the basal cisterns or surgical procedures that have allowed blood to accumulate around the major cerebral vessels in the basal cisterns (2,7,22). In most previously reported cases, neurological deterioration occurred between 5 and 10 days after resection of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…According to a very recent review, only 56 cases have been reported since the first cases in 1960 (2,13).…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes ranged from severe disability to full recovery. All authors encourage prompt diagnosis and treatment, as the high morbidity and mortality reported may be in part related to a delay in diagnosis [18, 19]. …”
Section: Discussionmentioning
confidence: 99%
“…The suspected vasospasm triggers discussed in these cases include chemical meningitis [9, 11, 24, 27], intraoperative bleeding, subarachnoid blood, intracranial hypotension, vasoactive tumor antigens, intraoperative vessel manipulation, and Gelfoam [19]. …”
Section: Discussionmentioning
confidence: 99%
“…In such clinical framework vasospasm should always be suspected at the occurrence of delayed onset neurological symptoms. The prevention and the rapidity of care may play a key role in patient recovery 2 . We describe a case of delayed symptomatic diffuse vasospasm especially involving the right anterior cerebral artery, following resection of a posterior fossa haemangioblastoma in an adult patient with von Hippel-Lindau (VHL) disease.…”
Section: Introductionmentioning
confidence: 99%